Opioid Prescribing After Curative-Intent Surgery: A Qualitative Study Using the Theoretical Domains Framework - Lee, Jay S.; Parashar, Vartika; Miller, Jacquelyn B.; Bremmer, Samantha M.; Vu, Joceline V.; Waljee, Jennifer F.; Dossett, Lesly A. (Annals of surgical oncology, 2018)
Background Excessive opioid prescribing is common after curative-intent surgery, but little is known about what factors influence prescribing behaviors among surgeons. To identify targets for intervention, we performed a qualitative study of opioid prescribing after curative-intent surgery using the Theoretical Domains Framework, a well-established implementation science method for identifying factors influencing healthcare provider behavior. Methods Prior to data collection, we constructed a semi-structured interview guide to explore decision making for opioid prescribing. We then conducted interviews with surgical oncology providers at a single comprehensive cancer center. Interviews were recorded, transcribed verbatim, then independently coded by two investigators using the Theoretical Domains Framework to identify theoretical domains relevant to opioid prescribing. Relevant domains were then linked to behavior models to select targeted interventions likely to improve opioid prescribing. Results Twenty-one subjects were interviewed from November 2016 to May 2017, including attending surgeons, resident surgeons, physician assistants, and nurses. Five theoretical domains emerged as relevant to opioid prescribing: environmental context and resources; social influences; beliefs about consequences; social/professional role and identity; and goals. Using these domains, three interventions were identified as likely to change opioid prescribing behavior: (1) enablement (deploy nurses during preoperative visits to counsel patients on opioid use); (2) environmental restructuring (provide on-screen prompts with normative data on the quantity of opioid prescribed); and (3) education (provide prescribing guidelines). Conclusions Key determinants of opioid prescribing behavior after curative-intent surgery include environmental and social factors. Interventions targeting these factors are likely to improve opioid prescribing in surgical oncology.